FAKTOR RISIKO KEJADIAN SKIZOFRENIA DI RUMAH SAKIT JIWA GRHASIA DAERAH ISTIMEWA YOGYAKARTA (DIY) - Handayani, Lina; Febriani, Febriani; Rahmadanni, Aprilia; Saufi, Azidanti (HUMANITAS, 2016)
AbstractSchizophrenia is a mental disorder that is quite widespread in nature in Indonesia, which is about 99% of patients, the mental hospital in Indonesia are people with schizophrenia. The highest prevalence of psychosis is in DIY is 2.7 per 1000 population. Based on the data reports the top 10 disease hospitalization from January to June 2015 at the Mental Hospital Grhasia DIY disease schizophrenia is a disease with a high of 371 while other mental disorders as many as 54 people. This study aimed to determine risk factors of schizophrenia in patients hospitalized in the Psychiatric Hospital Grhasia DIY. This research was an analytic observational with cross sectional design. The sample was 79 people schizophrenia and non-schizophrenia. Data analysis was using Fisher’s Exact Test. There were relationships between heredity RP = 1.195 (95% CI 1.004 to 1.423), psychosocial stressors of interpersonal relationship problems RP = 1.257 (CI95% from 1.056 to 1.497), psychosocial stressors of family factors RP = 1.366 (CI95% from 1.063 to 1.756) to the incidence of schizophrenia in-patients at the Mental Hospital Grhasia DIY. This research concluded that heredity, psychosocial stressors of interpersonal relationship problems and family factors are risk factors of the incidence of schizophrenia in the Mental Hospital DIY.Keywords: heredity, interpersonal relationship problems, psychosocial stressors, schizophreniaAbstrakSkizofrenia adalah gangguan mental yang cukup luas dialami di Indonesia, yaitu sekitar 99% pasien RS Jiwa di Indonesia adalah penderita skizofrenia. Prevalensi psikosis tertinggi adalah di DIY yaitu 2,7 per 1000 penduduk. Berdasarkan laporan data 10 besar penyakit rawat inap bulan Januari-Juni 2015 di Rumah Sakit Jiwa Grhasia DIY penyakit skizofrenia merupakan penyakit tertinggi yaitu dengan 371 orang sedangkan gangguan mental lainnya sebanyak 54 orang. Penelitian ini bertujuan untuk mengetahui faktor risiko kejadian skizofrenia pada pasien rawat inap di Rumah Sakit Jiwa Grhasia DIY. Jenis Penelitian ini adalah analitik observasional dengan rancangan cross sectional. Sampel penelitian ini adalah 79 pasien skizofrenia dan tidak skizofrenia. Analisis data dengan menggunakan uji Fisher’s Exact Test. Ada hubungan faktor keturunan RP= 1,195 (CI 95% 1,004-1,423), stresor psikososial dari masalah hubungan interpersonal RP= 1,257 (CI95% 1,056-1,497), stresor psikososial dari faktor keluarga RP= 1,366 (CI95% 1,063-1,756) dengan kejadian skizofrenia pada pasien rawat inap di Rumah Sakit Jiwa Grhasia DIY. Penelitian ini menyimpulkan bahwa faktor keturunan, stresor psikososial dari masalah hubungan interpersonal dan faktor keluarga merupakan factor risiko kejadian skizofrenia di Rumah Sakit Jiwa Grhasia DIY.Kata kunci: faktor keturunan, masalah hubungan interpersonal, stresor psikososial, skizofrenia